Colon in the Chest: An Incidental Dextrocardia. Issue 6 (February 2015) - Abd Elrazek, Abd Elrazek; Shehab, Abdullah; Elnour, Asim A.; Al Nuaimi, Saif K.; Baghdady, Shazly
Abstract : Abstract: Diaphragmatic injury is an uncommon traumatic injury (<1%). Although most diaphragmatic injuries can be obvious (eg, herniation of abdominal contents on chest radiograph), some injuries may be subtle and imaging studies can be nondiagnostic in many situations. Patients with diaphragmatic hernia either traumatic or nontraumatic may initially have no symptoms or signs to suggest an injury to the diaphragm. Here, we report a case of a 75-year-old woman diagnosed with irritable bowel syndrome –associated dominant constipation, presented with shortness of breath, cough, expectoration, tachycardia, and chest pain. Dextrocardia was an incidental finding, diagnosed by electrocardiography, chest radiograph, and CT chest. Parts of the colon, small intestine, and stomach were within the thorax in the left side due to left diaphragmatic hernia of a nontraumatic cause. Acquired incidental dextrocardia was the main problem due to displacement of the heart to contralateral side by the GI (gastrointestinal) viscera (left diaphragmatic hernia). The patient was prepared for the laparoscopic surgical repair, using a polyethylene mesh 20 cm to close the defect, and the patient recovered with accepted general condition. However, 5 days postoperative, the patient passed away suddenly due to unexplained cardiac arrest. Intrathoracic herniation of abdominal viscera should be considered in patients presented with sudden chest pain concomitant with a history of increased intra-abdominal pressure.